Chestnut blight (Cryphonectria parasitica (Murr.) Barr) disease incidence and its effect on the morphological and anatomical features of Castanea sativa trees - Keleş, Seray Özden; Ünal, Sabri; Akan, Sefer; Karadeniz, Mertcan (Wiley, 2024)
AbstractSweet chestnut (Castanea sativa) is an ecologically and economically valuable tree species worldwide. Various pathogens, both endemic or introduced, cause severe damage or death to chestnut trees. Chestnut blight, caused by the fungus Cryphonectria parasitica, is one of the most devastating plant diseases known which influences chestnut trees in all major cultivation regions. The work presented here aimed to investigate how the incidence of chestnut blight varied between trees growing at two altitudes (200–400 m vs. 400–600 m) and to determine the impact of chestnut blight on tree‐ring width, morphology and anatomy of C. sativa trees. The incidence of C. parasitica infections was greater at 200–400 m than at 400–600 m. Greater stem diameters were found at 200–400 m than at 400–600 m. There were no differences in stem diameters and heights, however, between healthy and C. parasitica infected chestnut trees. The anatomical characteristics of wood were also compared between healthy and C. parasitica‐infected chestnut trees. Fibre cell traits (length/width, lumen width, lumen area) were higher in healthy trees than in C. parasitica‐diseased trees. Vessel diameters were greater in infected compared with healthy trees. Tree ring widths and wood anatomical characteristics therefore were significantly influenced by C. parasitica infections.
Keywords: 15. Life on land